Taphofacies and Petrofacies Theoretical Marine Models Applied to the Coquina of the Amaral Formation (Lusitanian Basin, Portugal) - Garcia, Gustavo Gonçalves (2021)
The Amaral Formation has a wide geographic distribution within the Lusitanian Basin, at the western Iberian Margin (Portugal). The different depositional contexts for this unit enabled the distinction of three sectors: lagoon, lagoon-barrier, and marine-distal. The integration of the evolutionary taphonomic analysis of its fossil assemblages with the analysis of multiscale properties through the CAMURES methodology (Multiscale Reservoir Characterization) allowed the application of a methodology for the classification of coquina which was previously developed for the Morro do Chaves Formation (Sergipe–Alagoas Basin, Brazil). Here, it was adapted according to the complexity of the Amaral Formation deposits. The classification of ten taphofacies, in association with four lithofacies, allowed the definition of 84 petrofacies, based on the nature of the sedimentary and taphonomic processes. The relationship between the structural context, the systems tracts, the diversity of the fossil record, the classification of taphofacies and petrofacies, and the understanding of vertical and lateral variations of the sediments’ deposition within the unit support the construction of geological and theoretical models for coquina deposits. These models will allow for prediction of the spatial distribution of facies in other coquina analogous hydrocarbon reservoirs, as well as specifying the delimitation of reservoir zones for 3D geocellular modeling and flow simulation of hydrocarbon-producing reservoirs, thus improving predictive analyses.